Validasi Metode Analisis Cilostazol Dalam Plasma In Vitro Secara Kromatografi Cair Kinerja Tinggi - Harahap, Yahdiana; Mansur, Umar; Estherina, Christine (UI Scholars Hub, 2008)
Cilostazol is an antiplatelet agent with the mechanism of action by inhibiting phos-phodiesterase III (PDE III). Referred to Food and Drug Administration(FDA),cilostazol is a drug recommended to be bioequivalence (BE) studied. A high-perfor-mance liquid chromatographic (HPLC) method with ultraviolet detector for in vitro determination of cilostazol in human plasma had been developed and validated. Cilostazol and pioglitazone as internal standard were extracted from human plasma by protein precipitation method using methanol. The mobile phase consisting of ac-etonitrile-potassium di-hydrogen phosphate buffer 50 mM (40:60) was used at the flow rate of 1.5 mL/min on reversed phase C18 column (SunfireTM, 5 µm, 250x4.6 mm), and was detected at wavelength of 257 nm. Linearity was established within concentration range of 20-2000 ng/mL with coefficient correlation (r) was 0,9999. Accuracy (% diff) of this method was -14.67% up to 8.84% with precision (CV) being 0.98% to 4.93%, and absolute recovery was established to be 82.26% to 119.85%. Cilostazol in plasma was stable for 30 days in -200C storage.